Location fingerprint optimization based access point deployment in indoor WLAN localization - Mu ZHOU; Qiao-lin PU; Zeng-shan TIAN (Tongxin xuebao)
A novel access point (AP) deployment approach by optimizing the location fingerprints in indoor WLAN localization was proposed.Firstly,constructing the water-filling optimization model based on the maximum of the Euclidean distance of RSS between every two location fingerprints.Secoudly,after the process of the iterative cross-zero adjustment and discrete adjustment,the nonnegative and discrete weights of candidate AP locations were obtained.Finally,by using the criterion of maximum average weight,the APs,and consequently optimize the location fingerprints were deployed rationally.The experimental results demonstrate that the proposed approach is able to achieve high location fingerprint based localization precision,as well as consume low time overhead involved in the optimal AP location searching.